Efficacy of a solution-based approach for making sodalite waste forms for an oxide reduction salt utilized in the reprocessing of used uranium oxide fuel - Riley, Brian J.; Pierce, David A.; Frank, Steven M.; Matyáš, Josef; Burns, Carolyne A. (Journal of nuclear materials, 2015)
This paper describes the various approaches evaluated for making solution-derived sodalite with a LiCl–Li2O oxide reduction salt selected to dissolve used uranium oxide fuel so the uranium can be recovered and recycled. The approaches include modified sol–gel and solution-based synthesis processes. As-made products were mixed with 5 and 10mass% of a Na2O–B2O3–SiO2 glass binder and these, along with product without a binder, were heated using either a cold-press-and-sinter method or hot uniaxial pressing. The results demonstrate the limitation of sodalite yield due to the fast intermediate reactions between Na+ and Cl− to form halite in solution and Li2O and SiO2 to form lithium silicates (e.g., Li2SiO3 or Li2Si2O5) in the calcined and sintered pellets. The results show that pellets can be made with high sodalite fractions in the crystalline product (∼92mass%) and low porosities using a solution-based approach and this LiCl–Li2O salt but that the incorporation of Li into the sodalite is low.